2006
DOI: 10.1186/1471-2377-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vestibular neuritis: 3 cases with clinical features of acute vestibular neuritis, normal calorics but indications of saccular failure

Abstract: Background: Vestibular neuritis (VN) is commonly diagnosed by demonstration of unilateral vestibular failure, as unilateral loss of caloric response. As this test reflects the function of the superior part of the vestibular nerve only, cases of pure inferior nerve neuritis will be lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
5
28
0
5
Order By: Relevance
“…Ochi and Ohashi [14] observed in a patient with VN the absence of VEMP in the acute phase of the disease and its full recovery after 15 months. Monstad [5] described three patients, affected by VN, with the complete absence of VEMP and caloric test reflectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochi and Ohashi [14] observed in a patient with VN the absence of VEMP in the acute phase of the disease and its full recovery after 15 months. Monstad [5] described three patients, affected by VN, with the complete absence of VEMP and caloric test reflectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although past experiences highlight the importance of performing the VEMP together with the caloric test in the diagnosis of VN [2,5], some experiences show contrasting results: Murofushi et al [6] observed that VEMP is independent of the caloric stimulation results in 34% of patients with acute phase of VN; Halmagyi et al [7] described two cases of VN with normal response on caloric stimulation, but with no evocable VEMP.…”
Section: Introductionmentioning
confidence: 95%
“…Nach den bisherigen wenigen Berichten dominieren solche Schwindelempfindungen wie unbestimmtes Unwohlsein und Schwankschwindel [5,6,7,10]. Der für eine periphere vestibuläre Störung richtungsweisende Drehschwindel fehlt.…”
Section: Diagnosestellungunclassified
“…Die wichtigsten funktionsdiagnostischen Kriterien für eine Neuritis des N. vestibularis inferior sind somit die Konstellation einseitig fehlender ACcVEMP, erhaltene oVEMP, eine normale thermische Erregbarkeit und ein regelrechter Kopfimpulstest für den horizontalen VOR [4,6,10].…”
unclassified
“…The frequently occurring ocular tilt reaction [22] toward the affected side which can be observed directly through fundoscopy or be inferred from testing the subjective visual vertical (SVV) [24] is indicative of an utricular hypofunction as is an asymmetry ratio (AR) in ocular vestibular evoked myogenic potentials (oVEMPs). The saccular afferents from the vestibular organ as tested through cervical VEMPs frequently remain unaffected [14], but can also be dysfunctional [30,45]. The frequent sparing of the sacculus previously led to the conclusion that vestibular neuritis chiefly affects the superior vestibular nerve whilst sparing its inferior half in most cases [14].…”
Section: Introductionmentioning
confidence: 99%